Knowledge about folic acid supplementation before and during pregnancy among female medical fields students - Mroczek, Anna; Bałabuszek, Kamil; Pawlicka, Marta; Semczuk-Sikora, Anna (Journal of Education, Health and Sport, 2018)
Pregnancy is a period when optimal supply of vitamins and micro and macro elements is necessary to ensure proper fetal development and maternal health. One of the substances that has been shown to have a positive effect on the fetus is folic acid. Deficiency of this compound is associated with an increased risk of neural tube defects in the fetus. As a consequence, the awareness of women about the role of folic acid and necessity of its supplementation in the preconception period and during pregnancy is crucial. In order to obtain information on the knowledge of women regarding the need to take folic acid and the benefits associated with it, an anonymous questionnaire was carried out. The survey containing 28 original questions in an online form was sent to participants. The study showed deficiencies in the knowledge of female students of reproductive age regarding folic acid supplementation and the need to promote it. Therefore, it is necessary to include as many young women as possible to The Primary Prevention Program of Neural Tube Defects.